Eugeniusz Mironowicz, Polityka zagraniczna Białorusi 1990–2010 [Belorussian Foreign Policy in 1990–2010], TransHumana University Press, Białystok 2011, pp. 262 - Zakrzewska, Sylwia (The Copernicus Journal of Political Studies, 2018)
Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14761